PENGGUNAAN METODE ROLE PLAYING PADA MATA KULIAH MANAJEMEN SUMBER DAYA MANUSIA I (MSDM I) UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA JURUSAN MANAJEMEN - Fauzia Agustini; Hilma Harmen (LPPM Universitas Negeri Medan, 2012)
Success in a learning process can not be separated from the role of teacher during the process. In the learning process, lecturer can choose and use several methods of teaching that aims to make learning more interesting. This study aims to determine the effectiveness of role playing for Human Resources Management I subject in improving learning outcomes, level of creativity and liveliness of the third semester students of Management Department Faculty of Economic of Unimed. The technique of collecting data from this study is the result from pre test before action class research and the data from each cycle divided into first and second cycle. The sample used in this study were two classes A and B, total 75 students. The results showed that there was increasing in activity and learning outcomes of the students. The average score of pre test was 58, and from the first cycle increased to be 67 then the average of second cycle increased to be 81. Student activity in the affective aspect increased from cycle I to cycle II. In the first cycle, got percentage of average ability students were 35% (less successful), and on the second cycle increased to 84% (successful). Thus, it can be concluded that the role playing is effective for learning model to improve learning outcomes of the students from the first cycle to the second cycle.